Safety implications of high-field MRI: actuation of endogenous magnetic iron oxides in the human body. - Jon Dobson; Richard Bowtell; Ana Garcia-Prieto; Quentin Pankhurst (PLoS ONE)
Background Magnetic Resonance Imaging scanners have become ubiquitous in hospitals and high-field systems (greater than 3 Tesla) are becoming increasingly common. In light of recent European Union moves to limit high-field exposure for those working with MRI scanners, we have evaluated the potential for detrimental cellular effects via nanomagnetic actuation of endogenous iron oxides in the body. Methodology Theoretical models and experimental data on the composition and magnetic properties of endogenous iron oxides in human tissue were used to analyze the forces on iron oxide particles. Principal finding and conclusions Results show that, even at 9.4 Tesla, forces on these particles are unlikely to disrupt normal cellular function via nanomagnetic actuation.